Learning management strategy of communication studies through blended learning in higher education - K. Y. S., Putri; Abdullah, Zulhamri; Elisabeth, Nugrahaeni; Darmawan, Rachmat; Latifa, Latifa (International Association of Online Engineering, 2020)
This study aims to identify learning management strategies on communication studies through Blended Learning in Higher Education. This study uses a quasi-experimental method with a non-equivalent control group research design. This design uses two groups, namely the experimental group and the control group. Data collection was conducted with 82 Communication Studies students in 2019, Faculty of Social Sciences, Jakarta State University. Researchers also work with ethics communication lecturers and new media lecturers. The results of this study indicate that blended learning can increase students' knowledge of ethical communication. The average pretest value of the experimental class was 55.93, and the posttest value was 81.85. The average N-Gain in both the experimental class and the control class falls into the medium category. The average results of the N-Gain experimental class were higher at 0.56 compared to the control class at 0.36. Student learning attitudes in handling hoaxes get an average value of 2.99 while the control class is only 2.61. Although both of them have proper criteria, blended learning can also encourage participants to make the best use of face-to-face contact in developing knowledge. Thus, students are able to identify hoax news and implement it by providing information through social media to the public. The implications of this study provide convenience for lecturers in conducting learning strategies on learning ethical communication and new media for handling hoaxes.